"Facing the Challenge" – Drama and Citizenship Education in China - Xu, Jun; Yang, Tao (Cultural Arts Research and Development, 2022)
This essay will describe and discuss key ideas, trends and practices of citizenship and drama education in China. It will begin with a broad and brief reference to globalization as a means of explaining societal and education changes in China. The significance of citizenship education and drama education will be discussed in relation to how they exist in Chinese schools and in contexts beyond schools. Examples will be provided to demonstrate the challenges facing drama and citizenship teachers in China, either when working in their individual subject areas or attempting to find ways of working together. There begin with the landmark policies and important events in the field of drama and citizenship education in latest years, and describes the promising future for the progress of Chinese drama education from the perspective of increasing number of teachers. There will be references to other important drama theorists who have proved to be influential in China, particularly in the context of Drama and Citizenship education. In particular, the experiential reading project “Hunter Guolie” will be used to illuminate issues about the relationship between drama and citizenship education in China’s primary schools.